A Proposed Framework For Affordable CAM Replication In Cultural Heritage. Issue 1 (1st April 2022) - Korres, Georgios; Anagnostopoulos, Christos-Nikolaos; Eid, Mohamad
Abstract: The digital recording of cultural heritage artifacts and their replication with Computer-Aided Manufacturing (CAM) techniques has found many applications in the cultural heritage (CH) domain, and it is considered paramount. Although subtractive manufacturing comes with a tremendous financial cost since most of the hardware and the software used in the fabrication process are expensive and mainly proprietary. Consequently, many scholars benefit only from the cost-effective, easy-to-use, and prevalent additive manufacturing processes which can serve within certain limitations. In this work, we propose a framework to democratize the subtractive manufacturing processes required to replicate digitally recorded cultural heritage artifacts using open-source/license-free software and hardware tools. We further present an application of the framework by simulating the fabrication process of a laser-scanned bass relief using open-source and license-free CAM software as described in the proposed framework.